Situating ourselves in the problem: autoethnographic reflections on the construction of a feminist research project - Guizardi, Menara; Stefoni , Carolina; Gonzálvez, Herminia (Revista de Antropología Social, 2025)
The article presents an autoethnographic narrative about the embodied and situational dimension of the construction of a research proposal. We will analyze how the formulation of an ethnographic feminist project on the experiences of social scientists was part of a trajectory shared by the authors for almost a decade, intertwining work experiences and emotional ties. We will see that the motivation to propose the project –in its questions, objectives, methodologies– is woven from this common experience. We will start by discussing what we understand by a feminist (auto)ethnography, and recounting our journey as research colleagues: the dismantling of a network of academic women, the processes of editorial censorship, and our overloads of family care and professional work. We will then show how all this gave rise to a research proposal on gender inequalities in Latin American social sciences. We conclude by highlighting, from a feminist perspective, three critical aspects to situate ourselves in the research problem.